2010
DOI: 10.1111/j.1439-0442.1977.tb01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Retained Placenta in Cattle - Incidence, Clinical Data and Effects on Fertility

Abstract: Summary Data were collected from 1702 cows with retained placenta. All cows came from herds served by artificial inseminations, 72 per cent being Swedish red‐and‐white (SRB), 25 per cent Swedish Friesian (SLB) and 3 per cent other breeds. The incidence of retained placenta was higher after twin births and when the calves were stillborn. The sex distribution of the calves was normal. A positive correlation existed between retentio secundinarum and parturient paresis. On the other hand the incidence of ketosis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…A variety of methods have been used in the treatment of bovine RFM, although the efficacy of many of these treatments is questionable. Manual removal of the placenta remains a common practice despite numerous studies that fail to demonstrate a beneficial effect on reproductive performance or milk yield 59–62 . Recent prospective studies comparing manual removal and intrauterine antibiotic therapy along with systemic treatment of febrile cows found no difference in reproductive outcomes when compared with the use of systemic therapy of febrile cows alone 62,63 .…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…A variety of methods have been used in the treatment of bovine RFM, although the efficacy of many of these treatments is questionable. Manual removal of the placenta remains a common practice despite numerous studies that fail to demonstrate a beneficial effect on reproductive performance or milk yield 59–62 . Recent prospective studies comparing manual removal and intrauterine antibiotic therapy along with systemic treatment of febrile cows found no difference in reproductive outcomes when compared with the use of systemic therapy of febrile cows alone 62,63 .…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…[14] reported that the prevalence of retained placenta was higher in good condition, lower in fair and other in poor condition cows, respectively. These differences may be due to several risk factors such as uterine contractility, last calving type, body condition during , progesterone and oestrogen imbalance at parturition [6] , difficult delivery, age and parity of the cows [30] and other uterine infections, which predispose the cows to retention of after birth.…”
Section: Retainedmentioning
confidence: 99%
“…Existence of breed effects on retention of placenta studied by other authors. For examples, Dyranduhl et al (1977) found a higher incidence of the retention of after birth in Swedish Red and White than in Swedish Friesian. Saini et al (1988) recorded a higher retention of afterbirth among Temperate X Zebu.…”
Section: Resultsmentioning
confidence: 98%